2003
DOI: 10.1073/pnas.1734072100
|View full text |Cite
|
Sign up to set email alerts
|

Long-distance root-to-shoot transport of phytochelatins and cadmium in Arabidopsis

Abstract: Phytochelatin synthases (PCS) mediate cellular heavy-metal resistance in plants, fungi, and worms. However, phytochelatins (PCs) are generally considered to function as intracellular heavymetal detoxification mechanisms, and whether long-distance transport of PCs occurs during heavy-metal detoxification remains unknown. Here, wheat TaPCS1 cDNA expression was either targeted to Arabidopsis roots with the Arabidopsis alcohol dehydrogenase (Adh) promoter (Adh:: TaPCS1͞cad1 C admium is a widespread nonessential to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
234
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 308 publications
(253 citation statements)
references
References 34 publications
11
234
0
1
Order By: Relevance
“…Sweet potato seedlings grown in hydroponics were washed as described (Gong et al ., 2003) before sampling root and leaf tissues. The control plant tissues and plant tissues treated for Fe deficiency were digested in concentrated nitric acid for 5–7 days at room temperature, and the samples were boiled and completely digested.…”
Section: Methodsmentioning
confidence: 99%
“…Sweet potato seedlings grown in hydroponics were washed as described (Gong et al ., 2003) before sampling root and leaf tissues. The control plant tissues and plant tissues treated for Fe deficiency were digested in concentrated nitric acid for 5–7 days at room temperature, and the samples were boiled and completely digested.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, the role of PCs was thought to be limited to the intracellular detoxification mechanism by shuttling Cd 2+ -PC n complexes into the vacuole. However, recent studies on Brassica napus (Mendoza-Cózatl et al, 2008) and 22 Arabidopsis thaliana (Gong et al, 2003;Chen et al, 2006) showed that PCs could also play a major role in long-distance transport of Cd 2+ through xylem and phloem. Mendoza-Cózatl et al (2008) found that the concentration of PCs was 50 times higher in the phloem sap compared to the xylem sap and concluded that phloem was more active in transporting Cd 2+ from the source (older leaves) to the sink tissues (root, branches, younger leaves).…”
Section: + -Pc N Complex Formationmentioning
confidence: 99%
“…PCs may also have a role in the transport of Cu in the xylem or phloem tissues. It has already been shown that PCs can translocate from roots to shoots and vice versa, and that PCs mediate root-to-shoot transport of Cd (Gong et al, 2003;Chen et al, 2006).…”
Section: Functional Interaction Between Mts and Pcsmentioning
confidence: 99%
“…In particular, the cad1-3 mutant was shown to be PC deficient and hypersensitive to Cd toxicity due to a mutation in the AtPCS1 gene (Howden and Cobbett, 1992;Howden et al, 1995;Ha et al, 1999). Recent evidence also shows that PCs participate in transport of Cd from roots to shoots as a mechanism to alleviate Cd accumulation in Arabidopsis root cells (Gong et al, 2003).…”
mentioning
confidence: 99%